2010
DOI: 10.4103/0256-4947.71063
|View full text |Cite
|
Sign up to set email alerts
|

Comparing serum basal and follicular fluid levels of anti-Müllerian hormone as a predictor of in vitro fertilization outcomes in patients with and without polycystic ovary syndrome

Abstract: BACKGROUND AND OBJECTIVES:The prediction of in vitro fertilization (IVF) outcomes by anti-Müllerian hormone (AMH) measurement is getting increasing attention from clinicians. This study compares the relationship between serum or intrafollicular AMH levels and IVF outcomes in women with and without polycystic ovary syndrome (PCOS).METHODS:This prospective study was carried out in two university-based fertility clinics. Serum samples were collected on cycle day 3 and follicular fluid (FF) was collected on the da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 39 publications
2
25
0
1
Order By: Relevance
“…Studies in mice have identified the necessity of AMH in the preservation of the primordial follicle pool by inhibiting the follicular activation and growth as well as the follicle sensitivity to FSH [13,14]. Furthermore, data in the human reveal that serum AMH levels can be used as an ovarian follicular reserve marker [15,16], as well as a predictor of the ovarian responsiveness in normo-ovulatory women undergoing ovarian stimulation for IVF [17][18][19][20]. In addition, the importance of this hormone in the follicular recruitment arises from a number of studies, which correlate serum and follicular fluid AMH levels with the high number of 2-5 mm follicles in PCOS women [21][22][23][24][25], thus giving another clue to the clarification of the polycystic ovary syndrome pathology.…”
Section: Introductionmentioning
confidence: 98%
“…Studies in mice have identified the necessity of AMH in the preservation of the primordial follicle pool by inhibiting the follicular activation and growth as well as the follicle sensitivity to FSH [13,14]. Furthermore, data in the human reveal that serum AMH levels can be used as an ovarian follicular reserve marker [15,16], as well as a predictor of the ovarian responsiveness in normo-ovulatory women undergoing ovarian stimulation for IVF [17][18][19][20]. In addition, the importance of this hormone in the follicular recruitment arises from a number of studies, which correlate serum and follicular fluid AMH levels with the high number of 2-5 mm follicles in PCOS women [21][22][23][24][25], thus giving another clue to the clarification of the polycystic ovary syndrome pathology.…”
Section: Introductionmentioning
confidence: 98%
“…It inhibits the initiation of human primordial follicle growth and prevents multiple selection of a dominant follicle by reducing the sensitivity of follicles to follicle stimulating hormone (FSH) [1]. Several reports suggest that AMH might be a better predictor of ovarian responses to controlled ovarian hyperstimulation (COS) than traditional parameters such as age, FSH, estradiol (E 2 ) and inhibin B (INH-B) [7].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, studies have shown that AMH values can be influenced by comparable technical, physiological and exogenous factors [34]. Previous studies have shown that the range of AMH levels in PCOS patients is various [35][36][37], from 0.64 to 50.7 ng/ml [38]. However, these studies did not evaluate the ovarian response in these PCOS patients, we thus hypothesize that the AMH levels in the normal responders may be lower than those in the high responders.…”
Section: Discussionmentioning
confidence: 83%